Clinically relevant radioresistant cells exhibit resistance to H2O2 by decreasing internal H2O2 and lipid peroxidation. Issue 9 (September 2018) - Tomita, Kazuo; Kuwahara, Yoshikazu; Takashi, Yuko; Igarashi, Kento; Nagasawa, Taisuke; Nabika, Hideki; Kurimasa, Akihiro; Fukumoto, Manabu; Nishitani, Yoshihiro; Sato, Tomoaki
Radiation therapy is one of the choices to treat malignant tumors. In radiation therapy, existence of radiation-resistant cell is a major problem to overcome. We established clinically relevant radioresistant cells that had been obtained by exposing to 2 Gy/day X-rays for more than 30 days. These cells are resistant to 2 Gy/day X-ray exposure and anticancer agents. However, the underlying resistance mechanism remains unclear. We investigated the resistance of clinically relevant radioresistant cells to hydrogen peroxide (H2 O2 ), confirming a degree of resistance. Neither catalase enzyme activity nor aquaporins appeared to be involved in H2 O2 resistance. Mitochondrial DNA copy number, adenosine triphosphate (ATP) concentration, and plasma membrane potential were decreased. The timing of H2 O2 intake was delayed and lipid peroxidation was decreased. Sensitivity of clinically relevant radioresistant cells to H2 O2 was enhanced by 1-palmitoyl-2-(5′-oxo-valeroyl)-sn-glycero-3-phosphocholine administration. These results suggest that the membrane status is a major factor conferring H2 O2 resistance in clinically relevant radioresistant cells, and we should further investigate how membrane status could be used to enhance the therapeutic effect on cancer.